PERAN SEKERTARIS DESA DALAM PELAYANAN ADMINISTRASI PEMERITAHAN DESA KANONANG 3 KEC. KAWANGKOAN KAB.MINAHASA - WALANGITAN, CHARLA; PANGKEY, MASJE SILIJA; POMBENGI, JERICHO (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This research aims to explain about the role of Village Secretary in Administration Service ofKanonang Village Government 3. This research uses descriptive method of qualitative approach, and datacollection technique done by observation, interview technique and documentation. Number of informants asmany as 10 people. In this study using the administrative theory of village administration in terms of service tothe community, administration of village administration, and other matters relating to the village. The resultsshowed that the administrative service provided by the village government in this case that handles theadministrative process of the village that is the secretary of the village there are still shortcomings. This can beseen from the performance of village secretary in managing the correspondence of archival execution, reports,financial affairs, government administration affairs, development, and society. There are several things thatneed attention in the village officials in handling village government administration is to improve performanceand provide good service to the community by following the existing government administration mechanismsand procedures.Keywords: Role of Village Secretary in Administration Service of Village Government